Uma revisão sistemática sobre a produção científica com ênfase na poluição hídrica por metais pesados na bacia hidrográfica do río Quito - Colômbia: uma análise das complicações relacionadas à saúde humana e qualidade ambiental - Coelho, Bruna Stefane Rodrigues (Universidade Federal de São Carlos, 2023)
The pressures exerted on natural resources are increasing with each decade, especially on water resources, which, in addition to being a source of life, are essential for the development of important economic activities. In Latin America, a significant example of these pressures is the contamination of natural resources by heavy metals. Based on this scenario, the objective of the present study was to conduct a Systematic Literature Review (SLR) that could identify the historical evolution and the main activities related to water pollution by heavy metals in the Quito River watershed (Colombia) and the health and environmental complications arising from these activities. Through the SLR, it was possible to identify the contribution of mining activity to contamination in the study area, leading to impacts on water quality and availability, causing direct effects on the environment and the resident population of that area. Additionally, it was possible to document the main contaminants originating from the mining activity in the region, the contribution of universities to research the current conditions of the watershed, and the historical relationship between mining activity and drug trafficking. With this study, we obtained an overview of the current scientific production in the region and the main areas that need further investigation.
A systematic review of scientific production with emphasis on water pollution by heavy metals in the río Quito watershed - Colombia: an analysis of complications related to human health and environmental quality
Keywords: Chocó; Mineração; Contaminação; Meio Ambiente; Impactos; Mercúrio; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS